Effect of Leadership Style on Teacher’s performance of Private School in Nawalparasi - Sharma, Ganesh Prasad (Dibyajyoti Journal, 2024)
Exercising appropriate leadership, administrators might potentially alleviate the confusion resulting from the overlap of tasks in the work place, administration, and giving the directions within the top level of the management team work unit. The primary theory employed to assist this investigation was the Path-Goal Theory. The purpose of this study was to look into how school administrators' leadership philosophies impact the efficacy of their teachers. This study used a questionnaire as an instrument in a quantitative method survey design. In this investigation, a straightforward random sampling technique was applied. 212 administrators and teachers of private school from Nawalparasi are taken into consideration. Frequency, percentage, mean value, standard deviation, correlation Pearson were used to analyze the results. Furthermore, at the significance level of 0.95 both models of leadership have been showed the teachers effectiveness. In conclusion, administrators should consistently encourage, practice, and enhance these two leadership styles supportive leadership and participative leadership in order to boost the effectiveness of teachers at work.